Assessment of Once Daily Sustained Release Hydrophilic Matrix Tablet of Carvedilol - Kumar, Uttom; Islam, Md Samiul; Halder, Shimul; Rouf, Abu Shara Shamsur (Dhaka University Journal of Pharmaceutical Sciences, 2017)
The objective of the present study was to design and evaluate once daily sustained release tablet of carvedilol, using two molecular weight grades of hydrophilic polymers (methocel® K4M CR and methocel®K15M CR) as release retarding materials. Two sets of formulations were prepared, where first set of four formulations (F1- F4) contained variable ratios of methocel® K4M CR and methocel® K15M CR (15% : 15%, 15% : 13%, 15% : 11% and 15% : 9%) to optimize the composition of polymers in the tablet matrices such that the drug and polymer interaction was sufficient for sustaining release up to 24 hours and second set of five formulations (F5-F9) contained variable percentages of sodium lauryl sulfate (SLS) (1.0, 1.25, 1.5, 1.75 and 2.0%) to enhance the dissolution rate of the drug from the tablet matrices because of its poor aqueous solubility. The tablets were prepared by direct compression method and evaluated for hardness, thickness, friability, weight variation and in vitro drug release. The in vitro dissolution studies were carried out in simulated gastric fluid (900 ml, pH 1.2) for 24 hours using USP type II apparatus operated at 100 rpm and 37 ± 0.05°C. The release profiles were explored and explained by zero order, first order, Higuchi, Korsmeyer-Peppas and Hixson-Crowell models. From this study, the drug release profiles for formulations F6 to F9 were found to be satisfactory and the release mechanism followed both diffusion and erosion. Due to lower percentage of SLS used, F6 was considered as the best formulation. Dhaka Univ. J. Pharm. Sci. 16(1): 43-53, 2017 (June)